Opposing effects of sugar-free claims on perceived healthiness and sweetness reduce consumers’ willingness to pay for sugar-free products - Panidi, Ksenia; Grebenschikova, Yaroslava; Klucharev, Vasily; Shestakova, Anna N. (Frontiers in Nutrition, 2025)
BackgroundOverconsumption of sugar-enriched food remains one of the leading causes of obesity around the world. However, the question of whether consumers are willing to substitute sugar-containing products with their sugar-free analogues remains underexplored. One factor affecting consumers’ choices is their willingness to pay for sugar-free products. In the present study, we test the hypothesis that consumers are willing to pay more for sugar-free labeled products compared to their sugar-containing analogues, and that this effect is mediated by the subjective perceptions of product healthiness, tastiness, and sweetness induced by the label.MethodsIn our experiment, participants placed bids for sugar-containing and analogous sugar-free products in a Becker-deGroot-Marschak auction to determine their willingness to pay. Additionally, they rated each product on the level of perceived healthiness, sweetness, tastiness, and familiarity with the product. We then used structural equation modeling to estimate the direct, indirect, and total effect of the label on the willingness to pay.ResultsThe results suggest that, controlling for familiarity with the product, sugar-free labels significantly increased the willingness to pay due to the perception of sugar-free products as healthier than sugar-containing ones. However, this positive effect was overridden by a significant decrease in perceived tastiness and sweetness of products labeled as sugar-free compared to sugar-containing ones, which in turn led to a reduction in the willingness to pay. The overall effect of the label on the willingness to pay was, thus, insignificant. Additionally, we show that the effect of the label on perceived tastiness was fully mediated by perceived sweetness.ConclusionThe opposing effects of the label on subjective product perceptions may be limiting the efficiency of sugar-free claims in changing consumer choices towards healthier food options.